Paying them to hate US: The effect of U.S. military aid on anti-American terrorism, 1968-2018 - Eugen Dimant; Tim Krieger; Daniel Meierrieks (Albert-Ludwigs-Universität Freiburg, Wilfried-Guth-Stiftungsprofessur für Ordnungs- und Wettbewerbspolitik, 2023)
Does U.S. military aid make the United States safer? Or does it have unintended consequences for U.S. security? To answer these questions, we estimate the effect of U.S. military aid on anti-American terrorism for a sample of 174 countries between 1968 and 2018. We find that higher levels of aid especially for military financing and education increase the likelihood of anti-American terrorism in recipient countries. Examining potential transmission channels, we show that more U.S. military aid undermines military capacity and increases corruption and exclusionary policies in recipient countries. Our findings are consistent with the argument that military aid aggravates local grievances, creating anti-American resentment and leading to anti-American terrorism. Indeed, we also provide tentative evidence that military aid lowers public opinion about the United States in recipient countries.
Keywords: 330; Anti-American Terrorism; Corruption; Instrumental Variable Estimation; State Capacity; U.S. Military Aid